2016
DOI: 10.1007/s12237-016-0116-y
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Nitrogen Fixation: a Call for Re-evaluating Coastal N Budgets

Abstract: Coastal ocean primary productivity is often limited by nitrogen (N) availability, which is determined by the balance between N sources (e.g., N-fixation, groundwater, river inputs, etc.) and sinks (e.g., denitrification, sediment burial, etc.). Historically, heterotrophic N-fixation in sediments was excluded as a significant source of N in estuarine budgets, based on low, indirectly measured rates (e.g., acetylene reduction assay) and because it was unnecessary to achieve mass balance. Many recent studies usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 69 publications
2
48
0
Order By: Relevance
“…In addition, the nitrogen fixation rates was associated closely with C/N ratios in the intertidal sediments of the Yangtze Estuary ( r = 0.466, p = 0.014 in summer; r = 0.388, p = 0.045 in winter). This relationship shows that the quality of organic matter may play an important role in controlling the nitrogen fixation (Newell, McCarth, et al, ). Overall, the observed associations of benthic nitrogen fixation rates with organic matter imply that the nitrogen fixation is mainly heterotrophic in the intertidal sediments of the Yangtze Estuary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the nitrogen fixation rates was associated closely with C/N ratios in the intertidal sediments of the Yangtze Estuary ( r = 0.466, p = 0.014 in summer; r = 0.388, p = 0.045 in winter). This relationship shows that the quality of organic matter may play an important role in controlling the nitrogen fixation (Newell, McCarth, et al, ). Overall, the observed associations of benthic nitrogen fixation rates with organic matter imply that the nitrogen fixation is mainly heterotrophic in the intertidal sediments of the Yangtze Estuary.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition might be attributed to the additional energy cost associated with the conversion of N 2 gas to ammonium by diazotrophic bacteria, compared with direct assimilation of ambient ammonium (Bertics et al, ; Knapp, ). However, some studies have indicated that no inhibition on benthic nitrogen fixation occurs at high ammonium concentrations (Farnelid et al, ; Newell, McCarth, et al, ). This comparison demonstrated that diazotrophic bacteria might keep their function of fixing nitrogen regardless of the ambient nitrogen concentrations, and considerable nitrogen fixation occurs in the nitrogen‐enriched environments.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, N 2 : Ar has been shown to overestimate N 2 production in permeable sediments under advective pore‐water flow (Cook et al ), underestimated N 2 production in sediments reworked by macrofauna (Ferguson and Eyre ) and in estuarine sediments with hypoxic bottom water (Crowe et al ), and give comparable results (Eyre et al ; Deek et al ) relative to whole‐core‐IPT measurements. In some environments, applying both methods could be beneficial in studying benthic nitrogen fixation, which is now thought to be significant in a number of coastal systems (Fulweiler et al ; Andersson et al ; McCarthy et al ; Newell et al ). While this is attractive, this method comes with additional issues and the potential for determining incorrect rates ( see Eyre et al ).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Recent studies have revealed that N-fixation-the reduction of atmospheric N 2 to organic N-can play a larger role in coastal systems than previously thought (Fulweiler et al 2007;Andersson et al 2014;Newell et al 2016). Cyanobacteria have long been recognized as making a major contribution to Nfixation in illuminated aquatic sediments, however it is becoming increasing clear that other sediment microorganisms can make an important contribution to benthic N 2 -fixation (Severin and Stal 2010;Andersson et al 2014).…”
Section: Sediment N 2 Fixationmentioning
confidence: 99%
“…Several studies indicated that nitrogen fixation can occur in marine water with 200 μM of NH 4 + and/or 30 μM of NO 3 − (Farnelid et al, ; Newell et al, ). However, the negative effects of high NH 4 + and NO 3 − loading on NF occur in marine environments (Andersson et al, ).…”
Section: Discussionmentioning
confidence: 99%